IMPACT OF E-BANKING ON CUSTOMER PREFERENCES IN PRIVATE AND PUBLIC BANK IN TIRUNELVELI DISTRICT - G, Monisha; C. Kumari; Sweetlin Subi, G. (ShodhKosh: Journal of Visual and Performing Arts, 2024)
This study investigates the impact of e-banking on customer preferences within private and public banks. As digital banking services continue to evolve, understanding how they influence customer choices is crucial for both types of banking institutions. The research focuses on various dimensions of e-banking, including service accessibility, convenience, and technological innovations, to assess how these factors shape customer preferences. Key findings reveal that e-banking significantly enhances customer satisfaction by offering greater accessibility and convenience compared to traditional banking methods. Private banks, with their emphasis on advanced technology and personalized services, tend to attract customers who prioritize innovation and digital convenience. Conversely, public banks, known for their extensive branch networks and government backing, often appeal to customers who value reliability and traditional banking services alongside digital options. The study highlights that while private banks lead in adopting cutting-edge technologies, public banks are making strides in integrating e-banking features to improve service delivery and customer engagement. Both types of banks are increasingly focusing on enhancing their digital platforms to meet evolving customer expectations and preferences. Overall, the research underscores the growing importance of e-banking in shaping customer preferences and suggests that both private and public banks must continue to adapt their strategies to leverage digital advancements and improve customer experiences. Both primary and secondary has been collected. 100 respondents have been taken from Tirunelveli district. In those 50 respondents from private banks users and 50 respondents from public banks users.